KAJIAN PENILAIAN KINERJA SUNGAI BEKASI - Pipit Skriptianata Putra Pranida (Journal of Civil Engineering and Technology Sciences, 2023)
The Bekasi River is part of the Ciliwung-Cisadane River Region. The Bekasi River is an order 1 river from the Bekasi watershed which consists of 3 rivers, namely the Cileungsi River, Cikeas River and Bekasi River. The Bekasi River passes through Bekasi Regency. To determine the performance of a river, it is necessary to evaluate the physical condition and function of a river system, in accordance with the mandate from the Circular Letter of the Director General of Water Resources, Ministry of Public Works and Public Housing No. 05/SE/D/2016 dated 9 June 2016 concerning Guidelines for the Operation and Maintenance of River Infrastructure and River Maintenance. Assessment of the components of the Bekasi River facility based on Circular Letter Number 05/SE/D/2016 includes riverbeds, river banks, river banks, and river riparian areas. Assessment of the Bekasi River infrastructure components based on Circular Letter Number 05/SE/D/2016 includes river embankments, revetments, groves, flood spillways, flow control gates, flood pumps, rubber weirs, retention ponds, groundssill, inspection roads, H3 monitoring post buildings, Operation and Maintenance support buildings (laboratory, workshop, etc.), equipment infrastructure (heavy equipment, Operation and Maintenance vehicles), and information and communication equipment. The performance value of the Bekasi River condition is 77.85% and the performance value of the Bekasi River infrastructure is 79.30% so that the performance value of the Bekasi River is 78.58% which requires a type of Preventive maintenance.